(untitled) (Bangladesh Journal of Infectious Diseases, 2017)
Background: Typhoid fever varies according to different age and gender of the patients. Objective: The purpose of the present study was to observe different age and gender of typhoid fever patients among the paediatric group. Methodology: This cross sectional study was conducted at Department of Microbiology at Sir Salimullah Medical College, Dhaka, Bangladesh from January 2006 to December 2008 for a period of two (2) years. Blood samples from clinically suspected typhoid fever patients of different age and sex group was collected. Blood culture was done in all patients in the first week of illness. Widal test was done in all patients by using the first serum samples and in case of culture negative patients second serum samples (paired sera) were also tested by widal agglutination test. DOT Enzyme Immunoassay was also done in culture positive and culture negative typhoid patients by using the first serum sample. Result: A total number of 118(59%) paediatric patients were recruited. The highest rate of blood culture positivity for S. typhi was found among patients within 6 to 15 years of age group (19.14%). The rate of isolation of Salmonella typhi from blood of male patients were 19(15.1%) out of 126 cases and female patients were 11(14.9%) (P>0.05). The highest number of patients was in the low income group (72.5%). Highest number, 37(63.8%) patients were within the 6-15 years of age group followed by 13(22.41%) in 16-25 years age group. Conclusion: In conclusion typhoid fever mostly occurs in the age group of 6 to 15 years male patients with low socioeconomic status. Bangladesh Journal of Infectious Diseases 2016;3(2):36-39